Vulnerable atherosclerotic plaque metalloproteinases and foam cell phenotypes - Newby, Andrew C; George, Sarah J; Ismail, Yasmin; Johnson, Jason L; Sala-Newby, Graciela B; Thomas, Anita C (Thrombosis and haemostasis, 2009)
Plaque rupture underlies most myocardial infarctions. Plaques vulnerable to rupture have thin fibrous caps, an excess of macrophages over vascular smooth muscle cells, large lipid cores, and depletion of collagen and other matrix proteins form the cap and lipid core. Production of matrix metalloproteinases from macrophages is prominent in human plaques, and studies in genetically modified mice imply a causative role for metalloproteinases in plaque vulnerability. Recent in-vitro studies on human monocyte-derived macrophages and on foam-cell macrophages generated in vivo suggest the existence of several macrophage phenotypes with distinct patterns of metalloproteinase expression. These phenotypes could play differing roles in cap, core and aneurysm formation.